Hybrid Knot and Knotless Suture Anchor Repair for Patellar Tendon Rupture - Ekene U. Ezeokoli BS; Daniel Sutton MD; Theodore B. Shybut MD (SAGE Publishing, 2022)
Background: Patellar tendon ruptures are the third-most common injury involving the knee extensor mechanism. They typically occur in men under 40 years old as a result of eccentric quadriceps contraction while the knee is flexed and the foot is planted. 1 The optimal treatment is surgical repair within 2 weeks of injury to prevent scar formation, degeneration, and loss of tendon excursion. Indications: Operative management is generally indicated for patellar tendon ruptures. In this case, a physically active, healthy 24-year-old man presented with acute pain, extensor lag, and patella alta related to a basketball injury. He was diagnosed with acute patellar tendon rupture/extensor mechanism disruption and indicated for surgery. Technique description: We describe a technique for primary patellar tendon repair which uses both knot-based and knotless suture anchor fixation. Using a pulley effect, sutures in the inferior patellar anchors are used to reduce and repair the patellar tendon back to its bony origin. Patellar anchor-based tapes and a suprapatellar traction suture are affixed with knotless anchors to the proximal tibia to reinforce the repair. Anchor-based suture limbs are used to repair the medial and lateral retinacula. Results: The senior authors' experience with this technique has been excellent restoration of extensor mechanism function, with rehabilitation permitting early range of motion and no major complications or failures. This patient returned to unassisted activities of daily living between 8 and 12 weeks and had returned to gym workouts and recreational sports at 12 months. Discussion/conclusion: Biomechanical studies have demonstrated that compared with transosseous repair, suture anchor repair decreases gap formation and improves ultimate load to failure. Advantages of suture anchor repair include smaller incision, less tissue dissection, shorter operative time, and improved repair biomechanics. Our technique follows a principle of tendon repair using a high number of suture and tape limbs to span the repair. In addition, this technique incorporates a "double row" of suture anchors and spans the primary repair with a suture and tape "internal brace." The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.